2018
DOI: 10.1016/j.molmet.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Co-storage and release of insulin-like peptide-5, glucagon-like peptide-1 and peptideYY from murine and human colonic enteroendocrine cells

Abstract: ObjectiveInsulin-like peptide-5 (INSL5) is an orexigenic gut hormone found in a subset of colonic and rectal enteroendocrine L-cells together with the anorexigenic hormones glucagon-like peptide-1 (GLP-1) and peptideYY (PYY). Unlike GLP-1 and PYY, INSL5 levels are elevated by calorie restriction, raising questions about how these hormones respond to different stimuli when they arise from the same cell type. The aim of the current study was to identify whether and how INSL5, GLP-1 and PYY are co-secreted or dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 31 publications
2
58
0
Order By: Relevance
“…Steady-state Exendin-9 concentrations ( Figure 1H) were $0.4 mg/mL ($120 nmol/L), $2-fold above the binding affinity of Exendin-9 for GLP1R in human insulinoma cells (Waser and Reubi, 2011). PYY concentrations were higher after Exendin-9 than after placebo ( Figure 1I), mirroring the elevated GLP-1 levels and likely reflecting that PYY and GLP-1 are released from the same EEC type (Billing et al, 2018;Habib et al, 2013). Glucose-dependent insulinotropic polypeptide (GIP) concentrations were reduced by Exendin-9 ( Figure 1J), suggesting that endogenous GLP-1 enhances GIP secretion-a finding not previously reported.…”
Section: Role Of Glp-1 In Driving Hyperinsulinemia In Humansmentioning
confidence: 92%
“…Steady-state Exendin-9 concentrations ( Figure 1H) were $0.4 mg/mL ($120 nmol/L), $2-fold above the binding affinity of Exendin-9 for GLP1R in human insulinoma cells (Waser and Reubi, 2011). PYY concentrations were higher after Exendin-9 than after placebo ( Figure 1I), mirroring the elevated GLP-1 levels and likely reflecting that PYY and GLP-1 are released from the same EEC type (Billing et al, 2018;Habib et al, 2013). Glucose-dependent insulinotropic polypeptide (GIP) concentrations were reduced by Exendin-9 ( Figure 1J), suggesting that endogenous GLP-1 enhances GIP secretion-a finding not previously reported.…”
Section: Role Of Glp-1 In Driving Hyperinsulinemia In Humansmentioning
confidence: 92%
“…Furthermore, electron microscopy demonstrated that in cells coexpressing proglucagon product and PYY in human ileum, nearly all granules were labelled with GLP-1 and glicentin antisera, whereas a minority of vesicles contained PYY immunoreactivity (Eissele et al 1992). In the colon, GLP-1 and PYY are generally in the same vesicles (Billing et al 2018; Fothergill et al 2018). In fact, Billing et al (2018) found that GLP-1, PYY and INSL5 were generally costored in the same vesicles in murine colonic EECs.…”
Section: Storage Of Hormones At a Subcellular Levelmentioning
confidence: 99%
“…In the colon, GLP-1 and PYY are generally in the same vesicles (Billing et al 2018; Fothergill et al 2018). In fact, Billing et al (2018) found that GLP-1, PYY and INSL5 were generally costored in the same vesicles in murine colonic EECs. This is consistent with an electron microscope study showing that PYY and proglucagon-derived peptides are costored within secretory vesicles in cat colon and human rectum (Böttcher et al 1986).…”
Section: Storage Of Hormones At a Subcellular Levelmentioning
confidence: 99%
“…Once translated, the 180 amino acid long GCG protein is processed by two proteases, Psck1 and Psck3, to give GLP-1, GLP-2 but also the less studied and understood glicentin and oxyntomodulin ( 43 ). Other peptide hormones, such as insulin-like peptide 5 (INSL5) ( 44 , 45 ), PYY ( 46 ), GIP and neurotensin ( 17 , 47 ) can be co-expressed with the GCG products depending on the topographical localization of the cell; surprisingly, it appears that GLP-1 and PYY can be excreted independently possibly due to the existence of compartmentalized secretory vesicles ( 48 ).…”
Section: Chemosensation In Glp-1-producing Cellsmentioning
confidence: 99%